Analisis Resiko Daerah Rawan Kecelakaan pada Perlintasan Sebidang Kereta Api (Studi Kasus: Perlintasan Tarahan – Perlintasan Sukamenanti) - Meutia Nadia Karunia; Rahayu Sulistyorini; Aleksander Purba (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2019)
The accident rate between people and train actually can be reduced to minimum as the traffic of railway is not as crowded as road. This thesis is using stated prefence technique. Stated preference approaches with option statement in the form of hypothesis to be assessed by the respondent. With using regression analysis, researcher can see the dominant factors of the causes of railway-related accidents especially in Sukamenanti railway which is in a hypothetical situation. To determine the dominant factors causing accidents at railway based on the results of a questionnaire to the related instations to be compared with data on the number of train accident from 2012-2017 that obtained from the related instations with using regression analysis with the help of the SPSS program. The analysis result is: (the number of accidents from 2012-2017 ) = -9,256 + 0,008.X12+ 0,009.X6 + 0,011.X10 + 0,015.X5 From regression analysis result, dominant factors of railway-related accidents causes are inadequate railways, limited carriages, the inadequate of doorstop availability, the damages in engine, the factor of carriages age (X12), rider physic’s exhaustion while riding their vehicle (X6), Infrastructure damage such as worn rails, spaten railing, shovel rails, chained rails, cracked rail connections, skidding on rails, weathered bearings, incompatible ballasts, loose fitting, and unlocked wesel (X10), machinist’s body condition (exhausted)/sleepy while on duty (X5). Therefore the signification is a=0,05 with regression analysis test.